Quantitative optical lock‐in detection for quantitative imaging of switchable and non‐switchable components. Issue 10 (22nd July 2016) - Abbandonato, Gerardo; Storti, Barbara; Signore, Giovanni; Beltram, Fabio; Bizzarri, Ranieri
Abstract: Reversible photoswitching has been proposed as a way to identify molecules that are present in small numbers over a large, non‐switching, background. This approach, called optical‐lock‐in‐detection (OLID) requires the deterministic control of the fluorescence of a photochromic emitter through optical modulation between a bright (on) and a dark state (off). OLID yields a high‐contrast map where the switching molecules are pinpointed, but the fractional intensities of the emitters are not returned. The present work presents a modified OLID approach (quantitative OLID or qOLID) that yields quantitative information of the switching (fSW ) and non‐switching (fNS ) components. After the validation of the method with a sample dataset and image sequence, we apply qOLID to measurements in cells that transiently express the photochromic protein EYQ1. We show that qOLID is efficient in separating the modulated from the non‐modulated signal, the latter deriving from background/autofluorescence or fluorophores emitting in the same spectral region. Finally, we apply qOLID to Förster (Fluorescence) Resonance Energy Transfer (FRET) imaging. We here demonstrate that qOLID is able to highlight the distribution of FRET intensity in a sample by using a photochromic donor and a non‐photochromic acceptor.